INVESTIGATING EFL LEARNERS’ ABILITY IN APPLYING WRITING MECHANICS IN AN ARGUMENTATIVE ESSAY - M. Fadhly Farhy Abbas; Herdi Herdi (Proceedings of ISELT FBS Universitas Negeri Padang, 2018)
This study aims at investigating EFL learners’ ability in applying writing mechanics in writing an argumentative essay. Quantitative method with descriptive quantitative design was employed in this study. To collect the data, the writing test and unstructured interview were used in this research. This research was conducted on April 2018 at Universitas Lancang Kuning, Pekanbaru. There were 46 learners selected as participants in this research. The result of the writing test showed that the learners’ mean score was 64.6 and it was categorized into fair level of ability. Moreover, based on the interview the learners said that they felt difficult in applying good mechanics in their writing. It was beacuse the leraners had low alertness and carefulness in writing, low motivation to write an essay, low confidence when writing, and seldom to practice writing at leisure time. Therefore, appropriate writing strategy supported by suitable learning materials is needed to facilitate and improve the learners’ ability in applying writing mechanics in their writing. In conclusion, the learners’ ability in applying writing mechanics in an argumentative essay is in fair level of ability.